Analisis Pendekatan Technology Acceptance Model (TAM) Pada Penggunaan TikTok - Wati, Nursetia (Jurnal Teknologi Informasi Indonesia (JTII), 2022)
The purpose of this study was to describe the perceived influence on attitudes and adoption of Tiktok. Respondents in this study were 100 Tiktok users from various circles, with the provision that Tiktik users were at least 6 months in online trading. Questionnaire is an instrument method in data collection. And data analysis using SPSS. The research model uses the Technology Acceptance Model (TAM) based on the original variables, namely perceptions of ease of use, perceptions of use, usage attitudes, and actual use. The results show that ease of use has a positive and significant effect on usability in utilization. In other words, it can be said that if someone believes that the system is useful, then he will use it. In this study, it was also found that the attitude variable had a positive and significant effect on the intensity of system utilization. For further research, it is recommended to increase public interest/enthusiasm in using TikTok so that it is easy and useful, especially in terms of marketing products online